Pembelajaran Unggah Ungguh Basa Berbasis Assisted Learning sebagai Penanaman Karakter di Pendidikan Dasar - Nur Cholis, Nur Cholis (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study is to determine the effectiveness of Assisted Learning model to Mastering the level of speech Javanese as an effort to cultivate character birrul Walidain learners in elementary school. The method used in this research is experimental method. The population of the study were all the students of the fifth grade primary school in Sragen with the number of 13173. The sample was taken using stratified random sampling technique. The number of samples in this study were 100 students. Data collection was done by interviewing in depth interview method, observation and test method. The data collected in the form of score mastery level of Javanese language speech then analyzed using descriptive and inferential statistical analysis. The results showed that the level of significance showed 0,000 decision can reject H0 because the level of significance is less than from alpha (0.025). The difference can be seen from the calculation using the t-test that obtained the result tcount 21.611> ttable 1.98477. It can be concluded that there is influence of Assisted Learning model on the grading level of Javanese elementary school students. Students who have mastery of Javanese speech level is good and able to apply in the environment will have character birrul walidain especially in speaking.